RELIGIOUS MODERATION IN ISLAMIC RELIGIOUS PRACTICES THROUGH WASATHIYAH CONCEPT - ABDULLOH SAJJAD AHMAD (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2021)
Diversity is a natural event due to the meeting of various cultural differences in one place. Indonesia is a very plural and multicultural society. Diversity includes differences in culture, religion, race, language, ethnicity, ethnic traditions and so on. In such a multicultural society, tensions and conflicts between cultural groups often occur and have an impact on the harmony of life which can lead to imbalances and divisions. The purpose of this paper is to discuss religious moderation in the Indonesian context, religious moderation in Islamic religious practice through the concept of wasathiyah. The method used is a literature review. The conclusion in this study is that religious moderation is a religious attitude that is fair and balanced in viewing, responding and practicing between the practice of one's own religion (exclusive) and respect for the religious practices of other people with different beliefs (inclusive). In dealing with the diversity that occurs in Indonesia with its cultural diversity and its plural nature, it is necessary to strive for an increase in multicultural awareness in the Indonesian nation, and furthermore it will foster an attitude of religious moderation. The attitude of religious moderation is in the form of acknowledging the existence of other parties, having a tolerant attitude, respect for differences of opinion, and not imposing the will by means of violence. The concept of Islam wasathiyah, an inclusive way of Islam or an open religious attitude, which is called an attitude of religious moderation. In viewing and solving a problem, moderate Islam (wasathiyah) tries to take a compromise approach and is in the midst of its tribe, ethnicity, tradition, culture, and religion, is oriented towards islahiyah (good deeds) which is based on tradition, willing to listen to each other. and learn from each other to practice the ability to manage and overcome differences between them without compromising on the teachings of Islam that are believed. Keywords: Religious Moderation, Islamic Religious Practice, Wasathiyah Concept.